Gender Evaluation of Tomato and Eggplant in Koutiala and Bougouni Districts in Mali - International Institute of Tropical Agriculture (International Food Policy Research Institute, 2021)
Through research and scaling, Africa RISING strives to create opportunities for smallholder farm households to move out of hunger and poverty. However, knowledge about gendered differences in the adoption of intensification practices is still limited and often based on results from quantitative studies only. The Gender Evaluation of Tomato and Eggplant in Southern Mali study is conducted to gain an in-depth understanding of gender issues around the cultivation of tomatoes and eggplants. The data set covers demographic information, general farm system description, market participation, gender and household processes of 75 tomato and eggplant farmers in the Koutiala and Bougouni district of Southern Mali. The main data generation strategy of this study was focus group discussions.